New Landmines Against Georgia’s Statehood - Putkaradze, Tariel (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2013)
Since the proclamation of Georgia’s independence there have been attempts to stir up the opposition of inhabitants of Georgian historical provinces, ethnic Georgians or migrants resided in the given areas, against the central government. Referring briefly to the conflict in Abkhazia and Tskhinvali region I posit that in reality there are no so-called ethno-conflicts. In fact, in both cases groups ruled by the Russian empire, - among them consisting of not only ethnic Abkhazians, Russians, Armenians, and a part of Ossetians, but also a part of Georgians, - ran up against Georgian state. In this paper I deal with a factor – namely an artificial division of Georgia into regions, - aimed at encouraging the emergence of conflict centers. To make my arguments clearer I summon the code concerning the local governance approved by the Georgian government (31.10.2013); essentially the document consists of well-drafted statements. However, in the strained field of Geo-political ambitions within which the Georgian state operates – in the central part of the Caucasus – the document contains serious risks, namely, the VII chapter – “Regional Unification of Municipalities”. Above all, I would like to note that as a rule “the code on self-governance” should not have the paragraphs about the so-called “regional governance”. What is more important, when compared to the previous regulation the representative of central government in the given region becomes the first person of executive government of the regional representative council. I think that regional council, which at the present stage of development is confined, as if, to solely economic activities will (and not in the distant future) serve a purpose for tearing off some border territories of Georgia under the influence exerted by strong Geo-political neighbors. My conclusions are grounded by a certain number of circumstances: The dynamics of growth of functions of the so-called regional government; Deliberate narrowing of the semantics of the term “region”; Disregarding the historical context; Ignoring European regulations; Inaccurate reflection of the prospect of regaining occupied Abkhazia and Tskhinvali region.... I think Georgia should establish two levels of the self-governance, in which the first level will be represented in the villages and the second in the regional centers. As for the so-called “regional self-governance” it looks redundant in the country of small territories.